TANGGUNG JAWAB HUKUM DOKTER TERHADAP KONSULTASI VIA ONLINE APABILA PASIEN MENGALAMI KERUGIAN - Ramanda, Adi Tio Helga (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2021)
Health is the need of every human being in living his life. Health is also very important because without good health, it will be difficult for every human being to carry out his daily activities. Entering an era of rapid development, the world is faced with the emergence of new technologies in the medical field that allow doctors to practice in a virtual space. The legal basis of online medical services as well as to analyze the legal responsibility of doctors in providing online medical services if a patient experiences a loss. Type of research is a normative juridical research and analysis of legal materials. The approach used in this study is a statutory approach and a conceptual approach. Until now, there have been no detailed regulations regarding online-based medical services, both in statutory provisions and in the provisions of the medical code of ethics. Law Number 36 of 2009 concerning Health and Law Number 29 of 2004 concerning Medical Practice have so far not been used as a reference for the implementation of medical practice using online-based medical services. Furthermore, Law Number 11 of 2008 concerning Electronic Information and Transactions also cannot be used as a reference.